DEVELOPMENT OF EMBEDDED MINI-SENSOR FOR DIAGNOSIS OF CORROSION OF STEEL REINFORCEMENT IN CONCRETE NONDESTRUCTIVELY - Ismail, Mohamed; Lee, H.; Hussin, Mohd (2016)
Corrosion of steel reinforcement embedded in concrete is one of the main causes of degradation of reinforced concrete structures. Degradation occurs in reinforced concrete structures from corrosion caused by the Chloride ingress into concrete. That degradation has a severe impact on the structure in terms of maintenance and rehabilitation costs. Therefore, early detection of reinforcement corrosion is important for efficient maintenance, repair and planning. Meanwhile, the evaluation of the corrosion of reinforcement by non-destructive measurements have been used a lot. In particular CM-II (corrosion meter) is used to measure the polarization resistance, but has some disadvantages. Embedded mini-sensor has been developed in order to overcome these disadvantages. In this study, measurement of corrosion by using the mini-sensor is compared with the measured results by CM-II to verify the validity of the newly developed mini senor. Results show that there are agreement in trends of the parameters measured and as such the developed mini sensor has a promising start to be used.